The Leadership Role of the School Principal in Implementing Policies at MTS Hifzhil Quran - Rambe, Khoirunnisa Fadila; Syafiq, Zoe Zarka; Akmalia, Rizki; Farhana, Farhana; Tantri, Arya; Syevila, Siti (Continuous Education: Journal of Science and Research, 2023)
The leadership of the school principal has a very important role in implementing policies. In facing the complex challenges faced by the current education system, effective leadership is the key to achieving the goal of improving the quality of education. In acting as a leader, to be able to influence his elements, the principal must be able to provide an impact that must be respected by the educational implementing components within the educational institution. Therefore, the principal must be able to master the existing competencies of the principal. With this, the research method used is descriptive research, this research is used to be able to obtain a description of the role of the principal in implementing policies at MTS Hifzhil Quran which includes the role of the principal as a policy maker, teachers and students as implementers of the policy results provided by headmaster. In carrying out the duties of the school principal as the highest leader in an educational institution, the school principal does not only play his own role in making decisions or providing policies that will be implemented in the educational institution. With this, the school principal has several member components in determining the policies that will be implemented. Facilitation techniques used to help groups achieve common goals. The facilitator is responsible for building a conducive discussion process so that the group can reach a mutually beneficial agreement. In creating consensus or agreement, holding deliberations to obtain agreement through maintaining character is an important strategy in building consensus because the impact of officials who are able to maintain their own credibility will gain a place in the hearts of the community, the sense of admiration and sympathy shown by the community is the main key to creating agreement.